Density management diagram for teak plantations in Tabasco, Mexico - Minoche, Djhon (2017)
Density management diagrams are valuable tools for managing specific forestspecies. The aim of this study was to obtain a density management diagram for teak (Tectona grandis L.) plantations in the State of Tabasco in Mexico. To achieve this objective, a set of 10 plantations were studied, in which 42 plots were established. Two equations were fitted simultaneously, including one related to the quadratic mean diameter, stand density and dominant height and the other which related the total stand volume to the quadratic mean diameter, stand density and dominant height. The results showed that the diagram had an acceptable predictability, thus indicating its usefulness and accuracy in planning silvicultural interventions. This diagram is a very powerful tool that can enable stakeholders to manage teak plantations in the State of Tabasco.